Measuring the Temperature and Stress-Strain States of a Tube Sample under the Local Stochastic Temperature Pulsations - S. M. Dmitriev; R. R. Ryazapov; A. V. Mamaev; A. E. Sobornov; A. V. Kotin; M. A. Legchanov; A. V. Lvov (Приборы и методы измерений)
Provding a high level of durability of heat exchange equipment of water-cooled reactors under local stochastic temperature pulsations is an important scientific and technical problem for the nuclear power industry. Temperature pulsations produced by mixing non-isothermal coolant flows with high temperature gradient are most dangerous. This work is an experimental study of temperature and stress-strain state of a tube sample under local stochastic temperature pulsations caused by mixing of coolant flows.To solve the problems posed, a Y-junction with «counter injection» was built, which was included in the thermal-hydraulic research facility. The design of the Y-junction allows study of the thermal-hydraulic characteristics and durability of tube samples made of austenitic steel of 60 × 5 мм. Some tube samples had developed for measuring the temperature, stress-strain state of tube material and temperature field of coolant flow in mixing zone of single-phase coolants with different temperatures. Measuring tube samples were equipped with micro thermocouples and strain gauges.The experimental data of temperature pulsations, time-averaged temperature field in the coolant flow and on the outer surface of the sample were obtained, and statistical and spectral correlation characteristics of temperature pulsations were analyzed. According to results of measuring the relative strain, values of stresses were calculated.Devices and research techniques are developed. The combination of coolant flows parameters that provide thermal load of the metal surface at the highest level of stress intensity amplitude was obtained. The study results are used to verify the method for evaluating fatigue of reactor installations materials under stochastic temperature pulsations.